EVALUASI SIFAT FISIKA TANAH TYPIC HAPLUDULTS PADA EMPAT GENERASI TANAM KELAPA SAWIT PT SOCFIN INDONESIA DI KEBUN AEK LOBA KABUPATEN ASAHAN - Edison Parulian Sihombing Sihombing (Talenta Publisher, 2017)
Charges against oil palm plantations as the cause of soil degradation and as a ringleader ofenvironmental damage, drought land and take nutrients in large quantities make this studyimportant. The purpose of this study to determine the effect of oil palm cultivation on the four-generation of sustainable planting to changes in soil physical characteristics Typic hapludults. Description of soil profiles and sampling was conducted at four sites representinggenerations of planting oil palm. As the control mixed crop that has not been planted with oilpalm. Soil samples tested in the laboratory for each of the characteristics of soil physics.Results showed oil palm cultivation in soil Typic hapludults for four generations of plantscontinuously unchanged physical characteristics significant level. This shows that thecultivation of oil palm trees in a sustainable manner with the best management practicesystems PT Socfindo can maintain the physical characteristics of the soil.